The first Late Triassic Chinese triadophlebiomorphan (Insecta: Odonatoptera): biogeographic implications - Daran Zheng (Nature Portfolio, 2017)
Abstract The clade Triadophlebiomorpha represents a morphological ‘link’ between the Paleozoic griffenflies (Meganisoptera) and the modern taxa. Nevertheless they are relatively poorly known in the body structures and paleobiogeography. The Triassic dragonfly is extremely rare in China with only one previously recorded. A new family, Sinotriadophlebiidae Zheng, Nel et Zhang fam. nov., for the genus and species Sinotriadophlebia lini Zheng, Nel et Zhang gen. et sp. nov., is described from the Upper Triassic Baijiantan Formation of Xinjiang, northwestern China. It is the second Chinese Triassic odonatopteran and the second largest Mesozoic representative of this superorder in China. The discovery provides new information for the clade Triadophlebiomorpha during the Late Triassic and expands its distribution and diversity in Asia. The find reflects a close relationship between the two Triassic entomofaunas from Kyrgyzstan and the Junggar Basin, and provides a Carnian age constraint on the lowermost part of the Baijiantan Formation.